Paclitaxel-Induced Peripheral Neuropathy Using NCI-CTCin Isfahan, Iran: Paclitaxel-induced peripheral neuropathy - Mojhgan Aalam Samimi; Fariborz Mokarian; Amir Houshang Zargarzadeh; Mojhgan Abdolahi; Nasibeh Khadiby; Ali Basi (Iranian Journal of Pharmaceutical Sciences, 2008)
Paclitaxel is a highly effective anticancer agent. It is active against a broad range of cancers that are generally considered refractory to conventional chemotherapy.Paclitaxel induces a peripheral neuropathy (PN) that is characterized by sensory symptoms such as numbness and paresthesia in a glove and stocking distribution.PN may be severe and dose limiting at initial doses above 275 mg/m2. Our purpose was to evaluate the incidence, severity, dose dependency, and reversibility of paclitaxel-induced neuropathy. We studied 45 patients with breast cancer, treated with Paclitaxel (240, 270, 300 mg/m2) in an average of 4 cycles of treatment.Paclitaxel was administered by a 3 h intravenous infusion every 3 weeks in all patients.We used National Cancer Institute-Common Toxicity Criteria (NCI-CTC) to evaluate peripheral neuropathy. The cumulative dose of paclitaxel in each patient was also measured. The severity of symptoms was graded. Incidence and reversibility of neuropathy was measured in an interview with the patient. Paresthesias appeared in 39 (86.6%) patients after an average cumulative dose of 394 mg/m2.In most patients, PN was seen after the first or second dose (68%) of paclitaxel and then stabilized in 36%, improved in 36%, resolved completely in 24% and progressed in 4%. There was no need to discontinue Paclitaxel in any of the patients due to PN.In view of our experience in the present study, we found that Paclitaxel-induced neuropathy is a dose-dependent phenomenon, and most of the symptoms occurred after the first or second phase of treatment.